Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, October 4, 1896 - Julia Morgan::::::author::: (1896)
On October 4th, 1896 Julia Morgan writes her cousins Lucy and Pierre Le Brun with details of her whereabouts in Paris, France. She writes of her return to M. de Monclos atelier and still not knowing French. She tells that Mina is doing well and is going home in November. She mentions their trip to Switzerland and her future?hopes to travel in Southern France. She describes an encounter she has with a woman and her grandchildren at the garden at Cluny who are interested in America. The woman says her grandson is Augustus Saint-Gaudens, the sculptor. She describes the walks she takes to various sites around the atelier and the encounters she has.?